Beyond Rhetoric and Resistance: Institutional Pathways of Multiculturalism in Islamic Higher Education - Abidin Wakano; Saidin Ernas; Ummu Sai’dah; Fitria Lapele; Eko Wahyunanto Prihono (Jurnal Pendidikan Islam, 2025)
In an era of increasing cultural and religious diversity, higher education institutions worldwide are under pressure to foster inclusive environments that prepare students for pluralistic societies. This study examines how Islamic higher education in Indonesia navigates multiculturalism by analyzing three institutional cases through the lens of leadership agency, socio-religious context, and institutional culture. Drawing on document analysis, interviews, and classroom observations, the findings reveal three distinct pathways of institutional response. Case A represents a symbolic type in which inclusivity is expressed rhetorically but remains limited to events and public statements. Case B illustrates a substantive type in which multiculturalism is embedded in curricula, mentoring, and campus activities despite minimal rhetorical emphasis. Case C demonstrates a resistant type in which theological orthodoxy and structural homogeneity limit diversity initiatives and reinforce exclusionary practices. Together, these trajectories highlight that meaningful multicultural engagement depends not only on vision statements but also on the alignment of leadership commitment, curricular design, and institutional culture. The study implies that for Islamic education to move beyond rhetoric or resistance, it must embed multicultural values at both structural and cultural levels, thereby preparing students to engage constructively with diversity while remaining grounded in their religious identity.